Karakteristik Sifat Fisik Amplang Ikan Lele (Clarias sp) Dengan Penambahan Karagenan - Siti Nur Aisyah Jamil; Ulfatul Mardiyah; Linda Lutfiah (Samakia : Jurnal Ilmu Perikanan, 2024)
Fish is a perishable food so it needs to be handled appropriately, namely by processing it into a product in the form of amplang made from catfish. Catfish is a fish that is widely cultivated in Indonesia. Considering the abundant production of catfish, it is necessary to make variations, namely by adding carrageenan from the seaweed Euchema cottonii as a determinant of the physical and organoleptic properties of catfish amlang in the form of flowering power and organoleptic tests of color, taste, aroma, texture and crispness of amlang. The formulation of the problem in this research is how the addition of carrageenan affects the physical and organoleptic properties of catfish amlang and what is the best formulation for adding carrageenan to catfish amlang based on physical and organoleptic properties. Meanwhile, the aim of this research is to determine the effect of adding carrageenan on the physical and organoleptic properties of catfish amplang and to find out the best formulation for adding carrageenan to catfish amplang. This research is an experimental study using carrageenan as a determinant of physical and organoleptic properties in catfish amplang using 4 treatments (P0) as control, (P1) 1%, (P2) 2% (P3) 3%. Data were analyzed using the SPSS type 26 application with the ANOVA test at a confidence level of 95% with Duncan's advanced test. Meanwhile, to determine the best treatment, use the De Garmo method. The results of the research showed that the addition of carrageenan had a significant effect on the physical properties of catfish amplang's swellability, organoleptic attributes of color, taste, texture and crispness. However, the addition of carrageenan had no effect on the aroma attributes of catfish amplang. The best formulation for making catfish amplang is P1 treatment with the addition of 1% carrageenan based on the De Garmo method with a productivity value (NP) of 0.98.